Electromagnetic wave shielding materials, covering materials or exterior materials, and electrical and electronic equipment
By using a non-magnetic conductive metal layer as the outer layer in the electromagnetic wave shielding material and controlling Young's modulus and thickness, the cracks and interlayer floating problems of the material when bending are solved, ensuring the stability of the electromagnetic wave shielding effect.
Patent Information
- Application Number
- JP2022115828
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-07-20
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-07-20
AI Technical Summary
The existing electromagnetic wave shielding materials are prone to cracks or interlayer floating when bending, resulting in a decrease in the electromagnetic wave shielding effect, and the prior art does not fully consider the bending characteristics of the material.
A stacked structure is adopted in which at least one non-magnetic conductive metal layer and at least one ferromagnetic layer is used, wherein the non-magnetic conductive metal layer is used as the outer layer, and by controlling the Young's modulus and thickness of each layer, the curved neutral axis is located in the non-magnetic conductive metal layer to reduce cracks and interlayer floating.
It effectively suppresses the occurrence of cracks during the bending process of the material, and maintains the electromagnetic wave shielding effect, especially in the case of 180 degrees of bending or multiple bending.
Smart Images

Figure 0007627247000008 
Figure 0007627247000009 
Figure 0007627247000010
Abstract
Description
[Technical field]
[0001] The present invention relates to an electromagnetic wave shielding material, a covering material or exterior material, and an electric / electronic device. [Background technology]
[0002] In environmentally friendly automobiles equipped with secondary batteries, such as electric vehicles and hybrid vehicles, the direct current generated by the on-board secondary batteries is converted into alternating current via an inverter, and the necessary power is then supplied to an AC motor to obtain driving force. This causes electromagnetic waves to be generated due to the switching operation of the inverter, etc.
[0003] Electromagnetic waves are emitted not only from automobiles, but also from many other electrical and electronic devices, including communication devices, displays, and medical devices. Electromagnetic waves can cause precision equipment to malfunction, and there are also concerns about their effects on the human body.
[0004] Typically, in the high frequency range (1 MHz or higher), a conductive layer such as copper is known to exhibit good shielding properties against electromagnetic waves. However, in the low frequency range (less than 1 MHz), a conductive layer such as copper alone has low shielding properties against electromagnetic waves, so it is known that an electromagnetic wave shielding material formed by alternately laminating magnetic layers with excellent magnetic permeability and conductive layers exhibits good shielding properties against electromagnetic waves.
[0005] For example, Patent Document 1 proposes the following technology. "A noise suppression sheet used to suppress noise below 1 MHz, 1 ) and the magnetic layer (A n a noise suppression layer having n magnetic layers each having a thickness of 100 nm and at least (n-1) conductive layers, the magnetic layers and the conductive layers being alternately laminated, Each of the magnetic layers is represented by the following formula (1): i is 1 or more, X of each of the magnetic layers i The sum of is between 4 and 15, A noise suppression sheet, wherein each of the conductive layers has a proportional constant of 4 or more when the shielding property at 0.2 to 1 MHz is linearly approximated in magnetic field shielding property measurement by the KEC method. X i =√μ´ i ×√t i ...Equation (1) Here, n is an integer of 2 or more, and i is an integer of 1 or more and n or less. μ´ i is the magnetic layer (A i ) relative permeability at 1MHz, t i is the magnetic layer (A i ) film thickness [mm], It is.” [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2021-028940 Summary of the Invention [Problem to be solved by the invention]
[0007] Incidentally, electromagnetic wave shielding materials are sometimes used by being attached to cases, electronic components, etc. During use, the electromagnetic wave shielding material may be bent depending on the shape of the case or component, so there is a demand for an electromagnetic wave shielding material with excellent bending properties, such as bending close to 180° or bending multiple times.
[0008] Materials with high relative magnetic permeability that are generally used for the magnetic layer of an electromagnetic shielding material are often brittle, and when the electromagnetic shielding material is bent, cracks or the like may occur in the magnetic layer throughout its thickness direction. In addition, bending may cause layers that were joined to other layers to float. Such a phenomenon may be a factor in reducing the electromagnetic shielding effect in the noise frequency band. Patent Document 1 does not pay attention to the bending characteristics.
[0009] Therefore, an object of one embodiment of the present invention is to provide an electromagnetic wave shielding material that can effectively prevent cracks and the like from occurring during use (particularly when bent) as an electromagnetic wave shielding material. [Means for solving the problem]
[0010] The present inventors conducted extensive research to solve the above-mentioned problems and discovered that it is effective for at least one outermost layer of a laminate in which a ferromagnetic layer and a nonmagnetic conductive metal layer are stacked to be a nonmagnetic conductive metal layer, and for the neutral axis of bending when the laminate is bent with a curvature radius of 0.1 mm with the outermost nonmagnetic conductive metal layer facing outward to be located within the thickness of the outermost nonmagnetic conductive metal layer. As a result, they created the invention exemplified below.
[0011] [1] An electromagnetic wave shielding material having a laminate in which at least one nonmagnetic conductive metal layer and at least one ferromagnetic layer are laminated, At least one outermost layer of the laminate is a nonmagnetic conductive metal layer, An electromagnetic wave shielding material, wherein when the material is bent with a curvature radius of 0.1 mm with the outermost non-magnetic conductive metal layer facing outward, the neutral axis of bending is located within the thickness of the outermost non-magnetic conductive metal layer. [2] The electromagnetic wave shielding material according to [1], wherein the other outermost layer of the laminate is a ferromagnetic layer. [3] the Young's modulus of each nonmagnetic conductive metal layer is higher than the Young's modulus of each ferromagnetic layer; The electromagnetic wave shielding material according to [1] or [2], wherein the thickness of each nonmagnetic conductive metal layer is smaller than the thickness of each ferromagnetic layer. [4] The electromagnetic wave shielding material according to any one of [1] to [3], wherein the nonmagnetic conductive metal layer contains at least one selected from copper, a copper alloy, aluminum, and an aluminum alloy. [5] A covering or exterior material for electric / electronic devices, comprising the electromagnetic wave shielding material according to any one of [1] to [4]. [6] [5] An electric / electronic device comprising the covering material or exterior material according to the present invention. Effect of the Invention
[0012] According to one embodiment of the present invention, cracks and the like occurring during use (particularly when bent) as an electromagnetic wave shielding material can be effectively suppressed. [Brief description of the drawings]
[0013] [Figure 1] 1(A) and (B) are schematic diagrams for explaining the position of the bending neutral axis in a laminate, and FIG. 1(C) is a schematic diagram showing the directions of tensile stress and compressive stress acting when the laminate is bent. [Diagram 2] 2(A) to (D) are schematic diagrams for explaining the seam folding test. [Diagram 3] 1 is a graph showing the assumed bending strain of each layer of the electromagnetic wave shielding materials obtained in Example 1 and Comparative Examples 1 and 4.
[0014] The present invention is not limited to the following embodiments, and the components can be modified without departing from the spirit of the invention. In addition, various inventions can be formed by appropriately combining the components disclosed in the embodiments. In this specification, the term "neutral plane of bending" refers to a plane in which neither compressive stress nor tensile stress occurs when a bending moment is applied to an electromagnetic shielding material, and the term "neutral axis of bending" refers to the intersection between any cross-section of the electromagnetic shielding material and the neutral plane of bending.
[0015] [Electromagnetic wave shielding material] One embodiment of the electromagnetic shielding material according to the present invention has a laminate including at least one ferromagnetic layer and at least one nonmagnetic conductive metal layer, at least one outermost layer of the laminate being a nonmagnetic conductive metal layer, and the neutral axis of bending when the laminate is bent with a curvature radius of 0.1 mm with the outermost nonmagnetic conductive metal layer facing outward is located within the thickness of the outermost nonmagnetic conductive metal layer. In the present invention, it is sufficient to use materials that have substantially no variation in thickness of each nonmagnetic conductive metal layer and each ferromagnetic layer (within the allowable range of variation of ±2.5%), and the shape of each layer can be, for example, a sheet or foil.
[0016] As mentioned above, electromagnetic shielding materials may be bent when used. When bent, the length of the material from the neutral plane to the inside of the bend becomes shorter than the length before bending deformation, causing compressive stress to act, and the length of the material from the neutral plane to the outside of the bend becomes longer than the length before bending deformation, causing tensile stress to act. In particular, when an electromagnetic shielding material is bent with a relatively small radius of curvature, the layer on the outside of the bend is prone to cracking due to tensile stress. Such fractures cause a decrease in the shielding effect, as mentioned above. Therefore, in one embodiment, by appropriately controlling the Young's modulus and thickness of each layer of the laminate of the electromagnetic wave shielding material, the neutral axis of bending when bent with a relatively small radius of curvature is positioned within the thickness of the outermost non-magnetic conductive metal layer, making it possible to suppress the occurrence of cracks due to bending (for example, bending when attached to a housing, electronic component, etc.).
[0017] Next, the position of the bending neutral axis will be explained with reference to Figures 1(A), (B) and (C). For example, when bending is caused by an external force F in the thickness direction of the laminate, a bending moment M is generated, and a compressive stress (-σ) acts on the part on the inside of the bending neutral plane N, and a tensile stress (+σ) acts on the part on the outside of the bending neutral plane N. As shown in Figure 1(C), the tensile stress here is a stress that acts on the part on the outside of the bending neutral plane N in a direction pulling the part toward the side (tensile direction) of that part, and the compressive stress is a stress that acts on the part on the inside of the bending neutral plane N in a direction opposite to the pulling direction of the tensile stress (compression direction). From this, the Young's modulus of each layer, the thickness of each layer and the length L of a certain surface before bending deformation can be calculated. 0 From the length displacement ΔL of a certain surface before and after bending deformation, the position of the bending neutral surface where the stress is 0 (zero) is calculated based on the following numbers I to V. The length L of a certain surface before bending deformation shown in the following number I is calculated as 0 and the ratio of the length displacement ΔL of a certain surface before and after bending deformation, "ΔL / L0 " is the amount of strain on a certain surface inside the laminate after bending. Since neither tensile nor compressive stress acts on the neutral axis of bending, the length of the neutral axis of bending does not change before and after bending deformation. In other words, the amount of strain can be calculated by considering the ratio of the difference between the length of the neutral axis of bending and the length of a certain surface inside the laminate to the length of the neutral axis of bending. Also, as shown in the following equation II, the sum of the stresses acting on an infinitesimal area dA is the sum of tensile and compressive stresses, so it is 0 (zero), and this is also the case when i layers are laminated (see equation III). Also, according to Hooke's law "σ = Eε", the stress σ can be expressed as the product of Young's modulus E and the amount of strain ε, so using this and equation I, equation III can be transformed into equation IV. Then, in order to find the position of the neutral axis of bending, equation IV is transformed into equation V. Then, by substituting the numerical values corresponding to each parameter into equation V, the position of the neutral surface of bending can be found. The resulting "y 0 The value of " indicates the position of the neutral axis of bending.
[0018]
number
[0019]
number
[0020]
number
[0021]
number
[0022]
number
[0023] In one embodiment, in order to suppress cracks during bending, it is preferable that the other outermost layer of the laminate is a ferromagnetic layer. In addition, from the viewpoint of shielding properties, the ferromagnetic layer may be laminated via at least two nonmagnetic conductive metal layers. In addition, at least one surface of the nonmagnetic conductive metal layer may further have a treatment film of an alloy containing copper, and the above treatment film may further be provided on both surfaces of the nonmagnetic conductive metal layer. In this case, it is preferable that the treatment film is disposed via the ferromagnetic layer and the nonmagnetic conductive metal layer from the viewpoint of efficiently absorbing and attenuating electromagnetic waves in the ferromagnetic layer. The treatment film is formed, for example, on the surface of the ferromagnetic layer adjacent to the nonmagnetic conductive metal layer on the nonmagnetic conductive metal layer side. In addition, from the viewpoint of shielding properties, it is preferable that at least one outermost film (top film and / or bottom film) of the electromagnetic wave shielding material is a treatment film formed on the nonmagnetic conductive metal layer.
[0024] <Ferromagnetic layer> The ferromagnetic layer has electromagnetic wave absorbing properties, and has a relative permeability at a frequency of 1 MHz of approximately 10 to 50000. The ferromagnetic layer contains a magnetic metal material with high relative permeability, and examples thereof include a composite sheet in which the magnetic metal material and a resin are mixed and dispersed and integrally molded, a metal foil, and a laminate having high relative permeability in which a resin sheet is laminated on at least one surface of a metal foil, and the like. A composite sheet is preferred from the viewpoints of adhesion with the nonmagnetic conductive metal layer and reduction of distortion of the material when processing such as bending is performed. The relative magnetic permeability can be measured by any known method, and one example is a magnetic permeability measurement method using a BH curve tracer (see JIS C2560-2:2006).
[0025] When the ferromagnetic layer is a composite sheet or a laminate of a metal foil and a resin sheet, the resin may be a natural resin or a synthetic resin, and from the viewpoint of processability, a synthetic resin is preferable. These materials may also be mixed with fiber reinforcement materials such as carbon fiber, glass fiber, and aramid fiber. From the viewpoint of availability and processability, synthetic resins include polyesters such as PET (polyethylene terephthalate), PEN (polyethylene naphthalate), and PBT (polybutylene terephthalate), olefin resins such as polyethylene and polypropylene, polyamide, PI (polyimide), LCP (liquid crystal polymer), polyacetal, fluororesin, polyurethane, acrylic resin, epoxy resin, silicone resin, phenol resin, melamine resin, ABS resin, polyvinyl alcohol, urea resin, polyvinyl chloride, PC (polycarbonate), polystyrene, and styrene butadiene rubber, among which PET, PEN, polyamide, and PI are preferred for reasons of processability and cost. The synthetic resin may be an elastomer such as urethane rubber, chloroprene rubber, silicone rubber, fluororubber, styrene-based, olefin-based, PVC-based, urethane-based, or amide-based. Furthermore, the synthetic resin itself may play the role of an adhesive, in which case a structure is formed in which a nonmagnetic conductive metal layer is laminated via an adhesive. The adhesive is not particularly limited, but examples thereof include acrylic resin-based, epoxy resin-based, urethane-based, polyester-based, silicone resin-based, vinyl acetate-based, styrene butadiene rubber-based, nitrile rubber-based, phenolic resin-based, and cyanoacrylate-based adhesives, and from the viewpoints of ease of production and cost, urethane-based, polyester-based, and vinyl acetate-based adhesives are preferred. The composite sheet can be laminated in the form of a film or fiber. The composite sheet can also be formed by applying a mixed composition of an uncured magnetic metal material and a resin to the surface or treatment film of a nonmagnetic conductive metal layer and then curing the composition, but it is preferable to make the composite sheet affixable to the surface or treatment film of a nonmagnetic conductive metal layer for ease of production. For example, a PET film can be suitably used. By using a biaxially stretched film as the PET film, the strength of the electromagnetic wave shielding material can be increased. The mass ratio of the resin to the magnetic metal material in the composite sheet is, for example, 70:30 to 1:99.
[0026] When the ferromagnetic layer is a metal foil, it is more preferable that the ferromagnetic layer contains at least one selected from nickel, iron, permalloy (Ni-Fe alloy) and sendust (Fe-Si-Al alloy). These materials have relatively high relative permeability, so that they can collect magnetic flux components contained in noise and reduce the spatial magnetic field.
[0027] In one embodiment, the Young's modulus of the ferromagnetic layer is, for example, 0.2 to 10 GPa from the viewpoint of suppressing cracks and the like that occur during bending. By setting the Young's modulus within this range, it is possible to position the neutral axis of bending during a specified bending within the thickness of the outermost nonmagnetic conductive metal layer. The lower limit of the Young's modulus is, for example, 0.2 GPa or more, for example, 0.25 GPa or more, for example, 0.3 GPa or more, whereas the upper limit of the Young's modulus is, for example, 10 GPa or less, for example, 4 GPa or less. An example of a method for measuring the Young's modulus of the ferromagnetic layer is a static measurement method, and the measurement method described in the examples of this specification can be adopted.
[0028] In one embodiment, the thickness of each ferromagnetic layer is, for example, 5 to 200 μm from the viewpoint of suppressing cracks and the like that occur during bending. By setting the thickness within this range, it is possible to position the neutral axis of bending during a specified bending within the thickness of the outermost nonmagnetic conductive metal layer. The lower limit of the thickness per layer is, for example, 5 μm or more, and for example, 20 μm or more, whereas the upper limit of the thickness per layer is, for example, 200 μm or less, and for example, 100 μm or less. As an example of a method for measuring the thickness of the ferromagnetic layer, it can be measured using a constant pressure thickness measuring instrument (PG-20J, manufactured by Techclock) in accordance with JIS K6250:2019.
[0029] In one embodiment, when multiple ferromagnetic layers are formed, all the ferromagnetic layers may be made of the same material, or different materials may be used for each layer, and all the ferromagnetic layers may have the same thickness, or different thicknesses may be used for each layer.
[0030] Therefore, in the electromagnetic shielding material according to one embodiment of the present invention, the total thickness of the ferromagnetic layers is, for example, 5 to 300 μm. The lower limit of the total thickness is, for example, 5 μm or more, and for example, 15 μm or more, while the upper limit of the thickness per layer is, for example, 300 μm or less, and for example, 200 μm or less.
[0031] <Nonmagnetic conductive metal layer> The nonmagnetic conductive metal layer is made of a conductive metal material that exhibits diamagnetic or paramagnetic properties. In one embodiment, the material of the nonmagnetic conductive metal layer is not particularly limited, but from the viewpoint of improving the shielding properties against AC magnetic fields and AC electric fields, it is preferable to use a metal material with excellent conductivity. Specifically, the conductivity is 1.0×10 6 It is preferable that the conductive material is made of a metal having a conductivity of 10.0×10 S / m (value at 20°C; the same applies below), and the conductive material has a conductivity of 10.0×10 6 More preferably, it is 30.0×10 S / m or more. 6 It is even more preferable that the S / m is 50.0×10 6 Most preferably, the metal has a conductivity of about 39.6×10 S / m or more. 6 S / m of aluminum, conductivity is about 58.0×10 6 S / m of copper. In other words, in consideration of both conductivity and cost, it is preferable that the nonmagnetic conductive metal layer contains at least one selected from copper, copper alloy, aluminum, and aluminum alloy. These are preferable in terms of practicality.
[0032] In one embodiment, from the viewpoint of suppressing cracks and the like that may occur during bending, the Young's modulus of each nonmagnetic conductive metal layer may be higher than the Young's modulus of each ferromagnetic layer, for example, 40 to 250 GPa. The Young's modulus is, for example, 40 GPa or more, for example, 60 GPa or more, for example, 70 GPa or more, or for example, 80 GPa or more as a lower limit, while the Young's modulus is, for example, 250 GPa or less, for example, 200 GPa or less as an upper limit. Examples of methods for measuring the Young's modulus of the nonmagnetic conductive metal layer include a resonance method and a static measurement method, and the measurement methods described in the examples of this specification can be used.
[0033] In one embodiment, from the viewpoint of suppressing cracks and the like that occur during bending, the thickness of each nonmagnetic conductive metal layer is preferably smaller than the thickness of each ferromagnetic layer, for example, 6 to 150 μm per layer. By setting the thickness within this numerical range, it is possible to position the neutral axis of bending during a specified bending within the thickness of the outermost nonmagnetic conductive metal layer. In addition, the nonmagnetic conductive metal layer has appropriate ductility and good moldability. The lower limit of the thickness per layer is, for example, 6 μm or more, and for example, 12 μm or more, whereas the upper limit of the thickness per layer is, for example, 150 μm or less, and for example, 105 μm or less. The thickness of the non-magnetic conductive metal layer is measured by punching out a sample with a length of 150 mm and a width of 12.7 mm using a precision cutter, and the weight of the five punched test pieces is measured together and converted into thickness. For example, for rolled copper foil and electrolytic copper foil, test pieces are prepared as described above, their weights are measured, and the thickness is converted based on the specific gravity of copper. For aluminum foil, etc., measurements are made using a constant pressure thickness gauge (PG-20J, manufactured by Tecrock) in accordance with JIS K6250:2019.
[0034] In one embodiment, when multiple non-magnetic conductive metal layers are formed, all the non-magnetic conductive metal layers may be made of the same material, or different materials may be used for each layer, and all the non-magnetic conductive metal layers may have the same thickness, or different thicknesses may be used for each layer.
[0035] In one embodiment, the total thickness of the nonmagnetic conductive metal layers is, for example, 6 to 450 μm. The lower limit of the total thickness is, for example, 6 μm or more, and for example, 18 μm or more, while the upper limit of the thickness per layer is, for example, 450 μm or less, and for example, 315 μm or less.
[0036] The non-magnetic conductive metal layer is not particularly limited in shape, and may be, for example, a metal foil. When using copper foil as the metal foil, it is preferable that the purity is high because the shielding characteristics are improved, and the purity is preferably 99.5% by mass or more, more preferably 99.8% by mass or more. As the copper foil, rolled copper foil, electrolytic copper foil, metallized copper foil, etc. can be used, but rolled copper foil, which has excellent bending characteristics and moldability, is preferable. When alloy elements are added to the copper foil to make the copper alloy foil, the total content of these elements and unavoidable impurities may be less than 0.5% by mass. In particular, it is preferable that the copper foil contains at least one selected from tin, manganese, chromium, zinc, zirconium, magnesium, nickel, silicon, and silver in a total amount of 50 to 2000 ppm by mass, and / or phosphorus in a total amount of 10 to 50 ppm by mass, since the elongation is improved compared to that of a pure copper foil of the same thickness.
[0037] <Treated membrane> From the viewpoint of improving the shielding property, the treated film is formed on at least one surface of the non-magnetic conductive metal layer, and may further include at least one selected from an electromagnetic wave absorbing auxiliary film, a heat-resistant film, an anti-rust film, and a weather-resistant film, for example, an alloy containing copper. Examples of heat-resistant films that have been heat-resistant include plating films and vapor deposition films containing cobalt and nickel, examples of anti-rust films that have been rust-resistant include inorganic plating films such as zinc and chromium, vapor deposition films, and organic films such as benzotriazole, and examples of weather-resistant films that have been silane-coupling treated include organic coating films containing a silane coupling agent. That is, the treated film may further include at least one metal selected from zinc, molybdenum, tin, phosphorus, tungsten, chromium, and silicon in addition to copper, cobalt, and nickel. In addition, when the ferromagnetic layer is a composite sheet containing a resin, the treatment film interposed between the ferromagnetic layer and the nonmagnetic conductive metal layer can also increase the adhesion between the ferromagnetic layer and the nonmagnetic conductive metal layer.
[0038] The electromagnetic wave absorbing auxiliary film can be produced by a known method, for example, a plating process, a metal vapor deposition process, a sputtering process, etc. Among them, a method of forming an electromagnetic wave absorbing auxiliary film made of copper, cobalt, and nickel by plating the surface of a nonmagnetic conductive metal layer will be described below as an example. In the plating process for forming the auxiliary electromagnetic wave absorbing film, a particle film made of copper, cobalt and nickel is formed on at least one surface of the non-magnetic conductive metal layer.
[0039] (Plating conditions (roughening plating): copper, cobalt and nickel alloy plating) An example of the plating conditions for copper, cobalt and nickel is as follows. Liquid composition: Copper 10-20g / L, Cobalt 5-15g / L, Nickel 5-15g / L pH: 2~3 Liquid temperature: 30~50℃ Current density: 10~60A / dm 2 Coulomb amount: 10~48As / dm 2
[0040] In this case, the roughening plating treatment can be carried out in multiple stages under the above plating conditions.
[0041] (mass ratio, adhesion amount) When the mass ratio of nickel in each treatment film is 1, the mass ratio of cobalt in each treatment film is preferably 1.50 to 4.50. The lower limit of the mass ratio of cobalt is, for example, 1.50 or more, for example, 1.80 or more, or for example, 1.90 or more. The upper limit of the mass ratio of cobalt is, for example, 4.50 or less, or for example, 4.20 or less.
[0042] The mass ratio in the above-mentioned treatment film can be calculated based on the following formula (1). The mass ratio of cobalt in each treated film when the mass ratio of nickel in each treated film is 1 = [Co adhesion amount of treated film (μg / dm 2 ) / Ni adhesion amount of treated film (μg / dm 2 )] · · · (1)
[0043] In the heat-resistant treatment, on the aforementioned electromagnetic wave absorbing auxiliary film, at least one of the following heat-resistant films 1 to 8 can be further formed. The plating conditions and deposition conditions are shown below.
[0044] (Plating conditions for heat-resistant film 1) (Co-Ni plating: cobalt-nickel alloy plating) Liquid composition: Nickel 5-20g / L, Cobalt 1-8g / L pH: 2~3 Liquid temperature: 40~60℃ Current density: 10~30A / dm 2 Coulomb amount: 2~20As / dm 2
[0045] (Plating conditions for heat-resistant film 2) (Ni-Zn plating: nickel-zinc alloy plating) Liquid composition: Nickel 2-30g / L, Zinc 2-30g / L pH: 3~4 Liquid temperature: 30~50℃ Current density: 1~10A / dm 2 Coulomb amount: 0.5~2As / dm 2
[0046] (Plating conditions for heat-resistant film 3) (Ni-Cu plating: nickel-copper alloy plating) Liquid composition: Nickel 2-30g / L, Copper 2-30g / L pH: 3~4 Liquid temperature: 30~50℃ Current density: 1~2A / dm 2 Coulomb amount: 1~2As / dm 2
[0047] (Plating conditions for heat-resistant film 4) (Ni-Mo plating: nickel-molybdenum alloy plating) Liquid composition: Ni sulfate hexahydrate: 45~55g / dm 3 , Sodium molybdate dihydrate: 50-70g / dm 3 , Sodium citrate: 80-100g / dm 3 Liquid temperature: 20~40℃ Current density: 1~4A / dm 2 Coulomb amount: 1~2As / dm 2
[0048] (Plating conditions for heat-resistant film 5) (Ni-Sn plating: nickel-tin alloy plating) Liquid composition: Nickel 2-30g / L, Tin 2-30g / L pH: 1.5~4.5 Liquid temperature: 30~50℃ Current density: 1~2A / dm 2 Coulomb amount: 1~2As / dm 2
[0049] (Plating conditions for heat-resistant film 6) (Ni-P plating: nickel phosphorus alloy plating) Liquid composition: Nickel 30-70g / L, phosphorus 0.2-1.2g / L pH: 1.5~2.5 Liquid temperature: 30~40℃ Current density: 1~2A / dm 2 Coulomb amount: 1~2As / dm 2
[0050] (Plating conditions for heat-resistant film 7) (Ni-W plating: nickel-tungsten alloy plating) Liquid composition: Nickel 2-30g / L, Tungsten 0.01-5g / L pH: 3~4 Liquid temperature: 30~50℃ Current density: 1~2A / dm 2 Coulomb amount: 1~2As / dm 2
[0051] (Deposition conditions for heat-resistant film 8) (Ni-Cr deposition: nickel-chromium alloy deposition) A nickel-chromium alloy vapor deposition film is formed using a sputtering target having a composition of 65 to 85 mass % nickel and 15 to 35 mass % chromium. Target: Nickel 65-85 mass%, Chromium 15-35 mass% Equipment: Sputtering equipment manufactured by ULVAC, Inc. Output: DC50W Argon pressure: 0.2Pa
[0052] In the rust-proofing treatment, the following rust-proofing film and / or weather-resistant film can be further formed on the aforementioned electromagnetic wave absorbing auxiliary film or heat-resistant film. The respective conditions are shown below.
[0053] (Anti-rust plating conditions) Liquid composition: Potassium dichromate 1-10g / L, zinc 0.2-0.5g / L pH: 3~4 Liquid temperature: 50~70℃ Current density: 0~2A / dm 2 (0A / dm 2 is for immersion chromate treatment.) Coulomb amount: 0~2As / dm 2 (0As / dm 2 is for immersion chromate treatment.)
[0054] (Types of weather-resistant films (silane coupling films)) As an example, a diaminosilane aqueous solution or an epoxysilane aqueous solution can be applied. In addition, when a metal film such as a heat-resistant film or a plating film is formed by deposition (dry plating) such as sputtering, and when a metal film such as a heat-resistant film or a plating film is formed by plating (wet plating) and the metal film such as a heat-resistant film or a plating film is normal plating (smooth plating, i.e., plating performed at a current density less than the limiting current density), the metal film or plating film does not affect the surface shape of the copper foil. The limiting current density varies depending on the metal concentration, pH, solution supply rate, electrode distance, and plating solution temperature, but in the present invention, the limiting current density is defined as the current density at the boundary between normal plating (a state in which the plated metal is deposited in a film form) and roughened plating (burnt plating, a state in which the plated metal is deposited in a crystalline form (spherical, needle-like, frost-like, etc.), with unevenness), and the limiting current density is the current density (visual judgment) at the limit at which normal plating is obtained in a Hull cell test (just before burnt plating occurs). Specifically, the metal concentration, pH, and plating solution temperature are set as the plating production conditions, and a Hull Cell test is performed. Then, the state of metal layer formation (whether the plated metal is deposited in layers or formed in crystals) at the plating solution composition and plating solution temperature is investigated. Then, based on a current density chart made by Yamamoto Plating Tester Co., Ltd., the current density at the boundary between normal plating and roughened plating is obtained from the position of the test piece where the boundary exists. The current density at the boundary is defined as the limiting current density. This determines the limiting current density for the plating solution composition and plating solution temperature. In general, the limiting current density tends to be higher when the electrode distance is shorter. The method of the Hull Cell test is described, for example, in "Plating Practice Reader" by Kiyoshi Maruyama, published by Nikkan Kogyo Shimbun on June 30, 1983, pages 157 to 160. In order to perform plating at less than the limiting current density, the current density during plating is set to 20 A / dm 2 It is preferable to set it to 10 A / dm or less. 2 It is more preferable to set it to 8A / dm or less. 2 It is even more preferable that: Furthermore, the anti-rust film and weather-resistant film are extremely thin and do not affect the surface shape of the copper foil.
[0055] While the shielding characteristics improve as the number of laminations of ferromagnetic layers and nonmagnetic conductive metal layers increases, the neutral axis of bending may not be included in the nonmagnetic conductive metal layers on the outer side of the bend, which increases the number of lamination processes, leading to an increase in manufacturing costs and a tendency for the shielding improvement effect to saturate. Therefore, it is sufficient for the number of nonmagnetic conductive metal layers in the electromagnetic wave shielding material to be three or less, and for the number of ferromagnetic layers to be three or less. From the viewpoint of shielding properties, it is sufficient that the ferromagnetic layers and the nonmagnetic conductive metal layers are laminated alternately.
[0056] The lamination method of the ferromagnetic layer and the non-magnetic conductive metal layer may be performed by using an adhesive between the ferromagnetic layer and the non-magnetic conductive metal layer, or by thermocompression bonding of the ferromagnetic layer to the non-magnetic conductive metal layer without using an adhesive. Although a method of simply overlapping without using an adhesive may be used, in consideration of the integrity of the electromagnetic wave shielding material, it is preferable to bond at least the ends (for example, each side when the shielding material is rectangular) with tape, adhesive, or by thermocompression bonding. However, it is preferable to use an adhesive from the viewpoint of not applying excess heat to the ferromagnetic layer. The adhesive is the same as that described above and is not particularly limited, but examples thereof include acrylic resin, epoxy resin, urethane, polyester, silicone resin, vinyl acetate, styrene butadiene rubber, nitrile rubber, phenol resin, and cyanoacrylate, and urethane, polyester, and vinyl acetate are preferred for reasons of ease of production and cost.
[0057] The thickness of the adhesive layer is preferably 100 μm or less. If the thickness of the adhesive layer exceeds 100 μm, the bending neutral axis is likely to be located within the thickness of the adhesive layer or the ferromagnetic layer when bent, and the stress on the nonmagnetic conductive metal layer and the ferromagnetic layer, which are the layers to be bonded, becomes large, making them more likely to break. However, when the adhesive layer as described above also serves as the ferromagnetic layer, this is not the case, and the thickness can be as described in the explanation of the ferromagnetic layer. The Young's modulus of the adhesive layer is, for example, 50 to 10000 MPa. Examples of methods for measuring the Young's modulus include a static measurement method and a resonance method.
[0058] According to one embodiment, the magnetic shielding characteristic (how much the signal is attenuated on the receiving side) can be 15 dB or more at 100 kHz, preferably 18 dB or more, more preferably 20 dB or more, even more preferably 24 dB or more, and even more preferably 30 dB or more. In the present invention, the magnetic shielding characteristic is measured by the KEC method. The KEC method refers to the "electromagnetic shielding characteristic measurement method" of the Kansai Electronics Industry Development Center.
[0059] (Application) In one embodiment, the composition can be used for various electromagnetic shielding applications, such as covering or exterior materials for electric and electronic devices (e.g., inverters, communication devices, resonators, electron tubes, discharge lamps, electric heating devices, electric motors, generators, electronic components, printed circuits, medical devices, etc.), covering materials for harnesses and communication cables connected to electric and electronic devices, electromagnetic shielding sheets, electromagnetic shielding panels, electromagnetic shielding bags, electromagnetic shielding boxes, and electromagnetic shielding rooms. EXAMPLES
[0060] The present invention will be specifically described based on Examples, Comparative Examples, and Reference Examples. The following Examples, Comparative Examples, and Reference Examples are merely specific examples for facilitating understanding of the technical content of the present invention, and the technical scope of the present invention is not limited by these specific examples. In Table 1 and FIG. 3 below, "magnetic layer" means a ferromagnetic layer, and "metal layer" means a nonmagnetic conductive metal layer.
[0061] [Preparation of electromagnetic wave shielding materials] In Examples 1 to 9 and Comparative Examples 1 to 4, materials A to H were used, materials A to B were prepared as ferromagnetic layers, and materials C to H were prepared as nonmagnetic conductive metal layers, as shown in Table 1. Next, materials C to H were each subjected to an annealing treatment under conditions of a material temperature of 200° C. and a heating holding time of 0.5 hours. The materials A to H in Table 1 are as follows. An adhesive layer was formed on one surface of the composite sheets of materials A and B. The relative permeability values of materials A and B were listed with reference to the graphs in the catalog. Material A: Composite sheet (P100NH, Takeuchi Kogyo, relative permeability at a frequency of 1 MHz: approximately 130) Material B: Composite sheet (GM010S, Takeuchi Kogyo, relative permeability at a frequency of 1 MHz is approximately 24) Material C: Rolled copper foil (HA, made by JX Metal) Material D: Rolled copper foil (TPC (tough pitch copper, JX Metals, compliant with JIS H3100 C1100)) Material E: Electrolytic copper foil (JXEFL-V2, JX Metals) Material F: Electrolytic copper foil (commercially available) Material G: Aluminum foil (JIS A8021 standard, commercially available) Material H: Electrolytic copper foil (JX-UT, JX Metals)
[0062] For materials A to B, the Young's modulus was measured using a static measurement method. First, materials A to B were punched out using a precision cutter to a length of 160 mm and a width of 12.7 mm, and a tensile test was performed on the five punched test pieces. The test pieces that showed the maximum and minimum Young's modulus were excluded, and the average value of the Young's modulus of the remaining three test pieces was taken as the Young's modulus of the material. As conditions for the tensile test, the test piece was fixed to a test jig of a bench-top precision universal testing machine (Autograph AGS-X, manufactured by Shimadzu Corporation) so that the gripping length was 30 mm and the chuck distance was 100 mm, and then pulled in the length direction (longitudinal direction) at a speed of 50 mm / min, and the Young's modulus was calculated (JIS K7127:1999 standard). The Young's modulus of the materials C to G after the annealing treatment was measured using a resonance method. For the resonance method, a room temperature Young's modulus measuring device (TE-RT) manufactured by Nippon Technoplus Co., Ltd. was used. The materials C to G were cut into strips with a width of 10 mm and a length of 130 mm to obtain test pieces, and the measurements were performed using the test pieces. The Young's modulus of the material H after the annealing treatment was measured using a static measurement method. First, the material H was punched out using a precision cutter to a length of 150 mm and a width of 12.7 mm, and a tensile test was performed on five punched test pieces. The test pieces showing the maximum and minimum Young's moduli were removed, and the average value of the Young's moduli of the remaining three test pieces was taken as the Young's modulus of the material. The conditions for the tensile test were the same as those for the tensile tests of the materials A to B described above. The results are shown in Table 1.
[0063] Next, in Examples 1 to 4 and 7 to 9, the following (A) electromagnetic wave absorbing auxiliary film, (B) heat-resistant film, (C) rust-proof film, and (E) weather-resistant film were formed on the surfaces of the materials C to E, G, and H after the annealing treatment in the order of the following films as treatment films. In Example 5, the following (A) electromagnetic wave absorbing auxiliary film, (B) heat-resistant film, and (C) rust-proof film were formed on the surface of the material F after the annealing treatment in the order of the following films as treatment films. In Example 6, the following (A) electromagnetic wave absorbing auxiliary film was formed on the surface of the material G after the annealing treatment. In Comparative Examples 1, 3 to 4, the following (A) electromagnetic wave absorbing auxiliary film, (B) heat-resistant film, and (D) rust-proof film were formed on the surface of the material H after the annealing treatment. In Comparative Example 2, the following (A) electromagnetic wave absorbing auxiliary film, (B) heat-resistant film, (C) rust-proof film, and (D) rust-proof film were formed on the surface of the material H after the annealing treatment. The thickness of the treated film is submicron (10 -1 The formation time was appropriately adjusted so that the thickness of the nanoparticles was about 1 μm.
[0064] (A) Electromagnetic wave absorbing auxiliary film (Cu-Co-Ni alloy plating (roughening plating)) Liquid composition: Copper 15.5g / L, Cobalt 7.0g / L, Nickel 9.3g / L pH: 2.3 Liquid temperature: 36.0℃ Current density: (Top side) 1st time: 21.3A / dm 2 , 2nd time: 29.9A / dm 2 , 3rd time: 56.8A / dm 2 (Bottom side) 1st time: 14.9A / dm2 , Second time: 26.1 A / dm 2 , Third time: 56.8 dm 2 Coulomb quantity: (Upper surface) First time: 15.3 As / dm 2 , Second time: 21.5 As / dm 2 , Third time: 20.5 As / dm 2 (Lower surface) First time: 10.7 As / dm 2 , Second time: 18.8 As / dm 2 , Third time: 27.4 As / dm 2 (B) Heat-resistant film (Co-Ni alloy plating treatment) Liquid composition: Nickel 12.5 g / L, Cobalt 3.1 g / L pH: 2.0 Liquid temperature: 50 °C Current density: (Upper surface) 17.5 A / dm 2 , (Lower surface) 19.3 A / dm 2 Coulomb quantity: (Upper surface) 6.3 As / dm 2 , (Lower surface) 6.9 A / dm 2 (C) Rust-proof film (electrolytic chromate treatment) Liquid composition: Potassium dichromate 3.0 g / L, Zinc 0.33 g / L Liquid temperature: 55 °C pH: 3.65 Current density: (Upper surface) First time: 1.0 A / dm 2 , Second time: 1.0 A / dm 2 (Lower surface) 1.1 A / dm 2 Coulomb quantity: (Upper surface) First time: 0.7 As / dm 2 , Second time: 0.7 As / dm 2 (Lower surface) 0.8 As / dm 2 (D) Rust-proof film (benzotriazole treatment) Liquid composition: 40 mg / L Liquid temperature: 20 °C (room temperature) pH: 2.0 Current density: 0A / dm 2 (Shower spray treatment) Processing time: 5 seconds (E) Weather-resistant film (silane coupling treatment) Silane coupling agent: glycidoxypropyltrimethoxysilane Silane coupling agent concentration: 0.1 vol% Processing temperature: 20℃ (room temperature)
[0065] Next, in Examples 1 to 9 and Comparative Examples 1 to 4, the above surface-treated materials C to H were attached to the outer surfaces of the adhesive layers formed on the materials A to B, respectively, according to the configurations shown in Table 1. In this way, electromagnetic wave shielding materials were obtained in which the materials A to B and the above surface-treated materials C to H were laminated together.
[0066] <Evaluation method> (Seam folding test) The electromagnetic wave shielding materials obtained in Examples 1 to 9 and Comparative Examples 1 to 4 were subjected to a seam folding test in the following order. The results are shown in Table 1. (1) The electromagnetic wave shielding material was cut with a cutter to a size of 30 mm in width and 50 mm in length to prepare a test piece. (2) The test piece was lightly bent at 1 / 2 the length so that materials C to H were on the outside (see Fig. 2(A)), and then folded at 500 N for 1 second using a benchtop precision universal testing machine (Autograph AGS-X, manufactured by Shimadzu Corporation) (see Fig. 2(B)). (3) The test piece was returned to its original state (see Figure 2(C)). In the returned state, the sample was again pressed down with 500 N for 1 second using the bench-top precision universal testing machine (see Figure 2(D)). (4) After the above (3) was completed, the appearance of the measurement sample was visually confirmed. If it was confirmed that there were no cracks or peeling between materials A and B and materials C to H over more than half of the bent portion, the number of bends was confirmed by repeating the above (2) and (3). After bending, if peeling occurred between materials A and B and materials C to H, or if cracks occurred over more than half of the bent portion, further bending was discontinued. The number of seam folds in the table is the number of folds at the time when bending was discontinued minus 1. If the number of seam folds is 3 or more, the bendability is judged to be good.
[0067] (Estimation of the location of the bending neutral axis) When the electromagnetic shielding materials obtained in Examples 1 to 9 and Comparative Examples 1 to 4 were bent with a curvature radius of 0.1 mm with the nonmagnetic conductive metal layers C to H, which were the outermost layers, facing outward, the positions of the bending neutral axes within the thickness of each layer were calculated based on the above numbers I to V. The results are shown in Table 1. In addition, the thickness of the treated film is submicron (10 -1 Since the thickness of the treatment film was about 1 μm, the thickness of the treatment film was not used in calculating the location of the neutral axis of bending.
[0068] (Assumed bending strain) The expected bending strain at the surface layer of the material A, which is the ferromagnetic layer, and the expected bending strain at the surface layer of the materials C and H, which are the nonmagnetic conductive metal layers, of the electromagnetic shielding materials obtained in Example 1 and Comparative Examples 1 and 4 were calculated based on the positional relationship from the bending neutral axis (number VI). The results are shown in FIG. 3. According to FIG. 3, it can be seen that the bending neutral axis in Example 1, Comparative Example 1, and Comparative Example 4 is located at the metal layer (nonmagnetic conductive metal layer), the magnetic layer (ferromagnetic layer), and the interface, respectively. When the bending neutral axis is located in the ferromagnetic layer, tensile stress acts on the ferromagnetic layer, so the ferromagnetic layer, which is weaker against tensile stress than general metal materials, is more likely to break. In addition, when the bending neutral axis is located at the interface between the nonmagnetic conductive metal layer and the ferromagnetic layer, shear stress acts between the two materials, the nonmagnetic conductive metal layer and the ferromagnetic layer, so it is more likely to peel off. Therefore, by predicting the position of the bending neutral axis in the laminate, it is possible to predict the distribution of stress when bending and the ease of breaking.
[0069]
number
[0070] [Table 1]
[0071] (Discussion of the Examples) In Examples 1 to 9, the number of seam folds was 3 or more. As a result, in Examples 1 to 9, when the sheet was bent with a curvature radius of 0.1 mm with the outermost nonmagnetic conductive metal layer facing outward, the neutral axis of bending was located within the thickness of the outermost nonmagnetic conductive metal layer, which is presumably why cracks and the like can be effectively suppressed during use as an electromagnetic wave shielding material (particularly when bent). On the other hand, in Comparative Examples 1 to 3, the number of times of folding was less than 3. This is presumably because, when the sheet was bent with a curvature radius of 0.1 mm with the outermost nonmagnetic conductive metal layer on the outside, the neutral axis of bending was located within the thickness of the ferromagnetic layer, and tensile stress was applied to the ferromagnetic layer, which is weak against tensile stress, leading to breakage. In Comparative Example 4, the number of times the sheet was folded was less than 3. This is presumably because, when the sheet was bent with a curvature radius of 0.1 mm with the outermost nonmagnetic conductive metal layer on the outside, the neutral axis of bending was located at the interface between the nonmagnetic conductive metal layer and the ferromagnetic layer, so that the bending stress was 0 (zero), but the shear stress was at its maximum, causing the materials at the interface to peel off and leading to breakage.
Claims
1. An electromagnetic wave shielding material having a laminate in which at least one nonmagnetic conductive metal layer and at least one ferromagnetic layer are laminated, At least one outermost layer of the laminate is a nonmagnetic conductive metal layer, An electromagnetic wave shielding material, wherein when the material is bent with a curvature radius of 0.1 mm with the outermost non-magnetic conductive metal layer facing outward, the neutral axis of bending is located within the thickness of the outermost non-magnetic conductive metal layer.
2. The electromagnetic wave shielding material according to claim 1 , wherein the other outermost layer of the laminate is a ferromagnetic layer.
3. the Young's modulus of each nonmagnetic conductive metal layer is higher than the Young's modulus of each ferromagnetic layer; 3. The electromagnetic wave shielding material according to claim 1, wherein the thickness of each of the non-magnetic conductive metal layers is smaller than the thickness of each of the ferromagnetic layers.
4. 3. The electromagnetic shielding material according to claim 1, wherein the nonmagnetic conductive metal layer comprises at least one selected from the group consisting of copper, a copper alloy, aluminum, and an aluminum alloy.
5. A covering or exterior material for electric / electronic devices, comprising the electromagnetic wave shielding material according to claim 1 or 2.
6. An electric / electronic device comprising the covering material or exterior material according to claim 5.
Citation Information
Patent Citations
Electromagnetic wave shielding film and electronic component mounting substrate
JP2019009396A
Noise suppression sheet and laminate
JP2021028940A